A case of dyspnoea and visible neck pulsations. Issue 6 (13th January 2016) - Benny, Panakkal Jose; Rajesh, Gopalan Nair; Sajeev, Chakkanalil Govindan
Abstract : Clinical introduction: A 48-year-old male patient with a history of New York Heart Association (NYHA) Class II dyspnoea for the last 2 years presented with acute onset breathlessness associated with orthopnoea and palpitations. The symptom aggravation was abrupt with simultaneous occurrence of both dyspnoea and palpitations. After medical stabilisation, the neck pulsations were as shown in online supplementary video 1. Question: What is the most likely cardiac condition? Aortic regurgitation Congestive cardiac failure Tricuspid regurgitation Ventricular tachycardia